THU0544 ULTRASOUND EVALUATION OF UPPER LIMBS ENTHESES AND JOINTS IN HEALTHY CHILDREN. (June 2019) - Martire, Victoria; Collado, Paz
Abstract : Background: Enthesitis in children can result from mechanical or inflammatory processes. Enthesitis is a common finding in several JIA categories, particularly in ERA. Most of the available data on the potential application of ultrasound (US) for paediatric enthesitis is currently focused on lower extremity with limited data in upper extremity entheses. To know how normal US findings of extremities by age are lead to early diagnosis and might avoid misinterpretations. Objectives: To describe the age-related sonographic features of tendon insertions in the elbows and shoulders in healthy children. Methods: This is a prospective cross-sectional study of 43 healthy volunteer children. Selection criteria: free of musculoskeletal symptoms, medical conditions or medication affecting the MSK system assessed by a paediatric rheumatologist. Exclusion criteria: history of trauma/surgery, family history of spondyloarthritis and more than three hours of physical activity the previous week of the evaluation. Children were grouped according to age: group 1 (3–9 years, n=22), group 2 (10–13 years, n=12) and group 3 (14–18 years, n=9). The supraspinatus, common extensor, common flexor, and triceps tendon insertions were bilaterally examined in Power Doppler (PD) as well as grey-scale US using a GE Logic e machine with a linear transducer [8–13 MHz]. All entheses were evaluated in the longitudinal and transverse planes. Additionally, the corresponding joint was examined. Since there was no examination protocol available for scanning upper limbs entheses, a preferred US protocol for scanning children was used (1). Detailed description of entheses in grey-scale and Doppler modes was collected: echogenicity, thickness, presence of power Doppler signal (intra-entheseal at the bone/cartilage interface, peri-entheseal and within the unossified cartilage), as well as potential lesions (enthesophytes, erosions and calcifications). Measurement of tendon thickness was taken using US calipers at the site just where the tendon first contacts bone. All images were acquired by a single examiner (VM) and read by two readers. The inter-observer reliability for the tendon thickness measurements and Doppler signal was estimated between the two readers. Results: A total of 344 entheses were evaluated in 43 healthy children. Children had a median age of 9 years (IQR 6-13) and 55% were males. All the entheses appeared normal (homogenous fibrillar pattern) on grey-scale imaging. Mean tendon measurements are reported in Table 1 . In group 1, Doppler signal was seen in: supraspinatus (intracartilage) in one patient; common extensor (intra-entheseal) in 2 patients and triceps (intracartilage) in 1 patient. In group 2, common extensor (intracartilage) in 2 patients and common flexor in 2 patients (intracartilage) showed PD. None of the patients in group 3 exhibit PD signal. Children did not show either potential lesions on entheses or joint synovitis at shoulders or elbows. The ICC for entheseal measurement demonstrated high concordance 0.92 (0.84-0.93). Abbreviations: m: mean SD: standard deviation Conclusion: Tendon echogenicity was similar in all ages. Entheses thickness has a linear relationship with age. Detection of entheses Doppler signals at the bone/cartilage interface is rare, but its detection in the insertion to unossified cartilage may be taking account as a physiological finding in upper healthy limbs in younger children. References: [1] Collado P, Naredo E. Sonographic images of children's joints. Badalona (Spain): EUROMEDICE, Ediciones Medicas SL; 2007. Disclosure of Interests: None declared